BIM och organisationskommunikation i byggprocessen. En beskrivning av Skanska Stomsystems informationshantering. - Carlström,Pernilla (2013)
The construction industry has been criticized several times for failing to achieve the same productivity as other industries. BIM (Building Information Model/Modeling) is a revolutionary technology, and with a modern work method BIM has the ability to change the construction industry. The traditional paper-based information is changing into a virtual environment. A BIM- model does not automatically guarantee a complete solution, but it can contribute to an improved overall quality in the information management process. The purpose of this thesis is to describe the digital information management process at Skanska Stomsystem, by BIM. The study also intends to highlight the opportunities and deficiencies in the information management process. The study is limited to two different projects. The first step of this thesis was a thorough analysis of the current information management process at Skanska Stomsystem, to get a comprehensive overview. The research presented in this thesis is a qualitative case study that consists of an initial literature review, followed by qualitative interviews. The study shows that there are many benefits with BIM, for example it is time- and cost- efficient. But on the other hand there are also deficiencies, such as software compatibility and general lack of competence. On top of that it requires cultural changes, including new working methods, habits and change of routines. To improve the information management process, planning and communication are the success factors. Already in the early state of the construction process there should be clear goals and boundaries for each project.
Keywords: informationsflöde; bim; kommunikation; byggprocess; skanska